A Sharp Interface Method for Compressible Multi-Phase Flows Based on the Cut Cell and Ghost Fluid Methods (Advances in Applied Mathematics and Mechanics, 2018)
A new sharp interface method with the combination of Ghost Fluid Method(GFM) and Cut Cell scheme is developed to study compressible multi-phase flowswith clear interfaces. Straight-line cutting is applied on the cells passed by the interface.A new real-ghost mixing method is presented and applied around the cut cells todeal with very small cut cells. A cut face reconstruction method similar to volume offluid is applied to deal with topological change problems. A high order Level Set (LS)method is applied to evolve the free interface, with the Level Set velocities from exactRiemann solver on the cut faces. Various 1D and 2D numerical examples are tested toshow the robustness and ability of the present method in wide flow variable domains.This method benefits from cut cell on the sharp interface description, shows good conservationperformance, and does not have the topological change difficulty of the fullcut cell method presented in Chang, Deng & Theofanous, J. Comput. Phys., 242 (2013),pp. 946–990.